Improvement of Xylose Fermentation Ability under Heat and Acid Co-Stress in Saccharomyces cerevisiae Using Genome Shuffling Technique - Inokuma, Kentaro; Iwamoto, Ryo; Bamba, Takahiro; Hasunuma, Tomohisa; Kondo, Akihiko (Frontiers in Bioengineering and Biotechnology, 2017)
Xylose-assimilating yeasts with tolerance to both fermentation inhibitors (such as weak organic acids) and high temperature are required for cost-effective simultaneous saccharification and co-fermentation (SSCF) of lignocellulosic materials. Here, we demonstrate the construction of a novel xylose-assimilating Saccharomyces cerevisiae strain with improved fermentation performance under heat and acid co-stress using the drug resistance marker-aided genome shuffling technique. Two xylose-utilizing diploid yeasts with different genetic backgrounds were used as the parental strains for genome shuffling. The mutagenized genome pools derived from these strains were shuffled by sporulation and mating. The shuffled strains were then subjected to screening under co-stress conditions of heat and acids, and the hybrid strain Hyb-8 was isolated. The hybrid strain displayed enhanced xylose fermentation ability in comparison to both parental strains under co-stress conditions of heat and acids. Hyb-8 consumed 33.1 ± 0.6 g/L xylose and produced 11.1 ± 0.4 g/L ethanol after 72 h of fermentation at 38°C with 20 mM acetic acid and 15 mM formic acid. We also performed transcriptomic analysis of the hybrid strain and its parental strains to screen for key genes for multiple stress tolerances. We found that 13 genes, including five associated with cellular transition metal ion homeostasis, were significantly up-regulated in Hyb-8 compared to levels in both parental strains under co-stress conditions. The hybrid strain Hyb-8 has strong potential for cost-effective SSCF of lignocellulosic materials. Moreover, the transcriptome data gathered in this study will be useful for understanding the mechanisms of multiple tolerance to high temperature and acids in yeast and facilitate the development of robust yeast strains for SSCF.